LINGUISTIC ASPECTS OF POLITICAL DISCOURSE (TAMADDUN NURI JURNALI, 2024)
This article give brief information about linguistic aspects of political discourse as well as in line with the categorization of language levels namely morphological, lexical, and syntactic and the system of functional dominants of political discourse is examined, along with the primary theoretical and methodological approaches to the study of political speech.